Scientific Foundations of Organizing Oil Crop Seed Production - Xolboevich , Oripov Sherali; Ikromovich Mamarahimov Bunyоd; Musajanovich Tadjibaev Baxtiyаr (American Journal of Biology and Natural Sciences, 2026)
To date, 180,000 hectares of oilseed crops have been sown in our republic. However, due to improperly organized seed production systems under production conditions, the potential for increasing yields is limited. This article provides information on the development of a seed production system and the basic requirements for seed material. Seed production is considered one of the most important measures for increasing crop yields and agricultural production in our country. Scientific advancements and advanced production experience indicate that a modern, properly organized seed production system increases crop yields by 20-25 percent. The goal of the seed industry is to multiply the seeds of regionalized (state-registered) varieties while maintaining varietal purity and biological and economic characteristics.